The linear elastic in-plane bending of curved hollow profiles having a thin-walled rectangular section - Melo, F. J. M. Q. de
This paper presents a simple solution for the flexibility calculation of curved profiles having a rectangular thin-walled cross-section. Some assumptions related to geometric details about the shape of the deformed structure are included in the present analysis, aiming at an economic and accurate solution. Results concerning the distortion of the transverse section are compared with the corresponding data from the solution with a thin shell finite element analysis. A flexibility factor for the structure analysed here is presented as a graphical result.